HUBUNGAN KONSENTRASI KARBON MONOKSIDA (CO) DAN FAKTOR-FAKTOR RESIKO DENGAN KONSENTRASI COHb DALAM DARAH PADA MASYARAKAT BERESIKO DI SEPANJANG JALAN SETIABUDI SEMARANG - Muttia Hazsya; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Semarang is one of the big cities in Central Java Province. The increase of vehicles that pass through various roads in Semarang city one of the factors for pollutant in the air through exhaust gas emitted from the vehicles namely carbon monoxide (CO) which affects health, which is the presence of COHb concentration in a person’s blood that will cause the decrease in blood capacity to bond oxygen. This research aims to analyze the relationship of carbon monoxide gas and COHb concentration in blood of at-risk people around Setiabudi Street, Semarang. Previous research states that high COHb concentration in blood is at the average of 5,4%. The population in this research is Setiabudi Street Semarang, which is divided into 3 locations with 11 respondents who are chosen at each point. The subject of this research is 33 respondents. The technique used in this research is quota sampling. The result of carbon monoxide gas concentration at Setiabudi Street were in the range of 11.878-13.431 µg/m3, and by using Spearman Rank test showed that there was no relation between CO concentration COHb concentration with (p=0,13). Using Pearson test showed that there was a relationship between exposure time (p=0,002) and smoking habit (0,009) with COHb concentration in blood that was the risk factor for COHb concentration in blood. The conclusion of this research is the concentration of COHb in the blood is closely connected with the exposure time and smoking habit.